Tetra-aqua-(4,4'-bimethyl-2,2'-bipyridine)-nickel(ii) sulfate hydrate: a simple structure with an extremely complex H-bonding scheme. - Suarez, Sebastian; Doctorovich, Fabio; Harvey, Miguel Angel; Baggio, Ricardo Fortunato (International Union of Crystallography, 2013)
Fil: Suarez, Sebastian. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Industrias; Argentina